IDENTIFICATION OF MASSIVELY MULTIPLAYER ONLINE GAME ADDICTION FACTORS FOR MALAYSIAN ADOLESCENT USING FOCUS GROUP DISCUSSION - M. SALIH, MUHAMMAD MUHAIMIN (2019)
Online games have become one of the most popular games and frequently played among adolescents. Adolescents who are experiencing loneliness and inadequate social skills have more tendency to play online games. Even though this range of people usually benefits from online interactions, but they might suffer more from negative after-effects. In fact, adding up other additional problems besides loneliness in their lives, the accumulation of problems would drive them to stay addicted on online activities, as it believes in helping them in escaping their real-life problems. Both addiction and abuse of online games will correlate with negative impacts rather than positive impacts.